2002
DOI: 10.1007/s00423-002-0326-6
|View full text |Cite
|
Sign up to set email alerts
|

Indirect lymph node lymphangiography using an iodine-based contrast medium and projection radiography following submucosal injection in a rabbit model

Abstract: This method appears useful when investigating local lymph nodes following submucosal injection due to its passage into lymphatic vessels and storage in lymph nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Tanaka et al (35) reported the incidental lymph node uptake of ethiodized oil after submucosal injection during CT examinations to evaluate the extent of esophageal cancer spread. Also, some previous reports (36, 37) demonstrated the regional lymph node uptake of ethiodized oil based contrast media with mural injection into the stomach of gastric cancer patients (36) and with submucosal injection into the rectum of healthy rabbits (37). However, these studies used simple radiography instead of CT examination.…”
Section: Discussionmentioning
confidence: 93%
“…Tanaka et al (35) reported the incidental lymph node uptake of ethiodized oil after submucosal injection during CT examinations to evaluate the extent of esophageal cancer spread. Also, some previous reports (36, 37) demonstrated the regional lymph node uptake of ethiodized oil based contrast media with mural injection into the stomach of gastric cancer patients (36) and with submucosal injection into the rectum of healthy rabbits (37). However, these studies used simple radiography instead of CT examination.…”
Section: Discussionmentioning
confidence: 93%